Efektivitas Pemanfaatan Komik sebagai Media Pembelajaran Matematika - Erlanda Nathasia Subroto; Abd. Qohar; Dwiyana Dwiyana (Graduate School of Universitas Negeri Malang, 2020)
Abstract: This study aims to determine the effectiveness of the use of comics as a media in mathematics learning. This research was conducted in home schooling